An Analysis of Managerial Competence of the Madrasah Principals in Islamic Senior High School in Tanah Datar - Asmendri Asmendri; Sufyarma Marsidin; Rusdinal Rusdinal; Mukhaiyar Mukhaiyar (AT-TA'LIM, 2018)
Based on preliminary observation and research finding in MAN in Tanah Datar, it was found that madrasah which have a good accreditation still have problems concerning with aspects of school management. The purposes of this research were to analyze teachers’ perception toward managerial competence of the madrasah principals in the aspects of the madrasah activities planning, organizing, leadership, actuating, and controlling. The methodology used in this research was mixed method by using the concurrent embedded model. Quantitative data was gotten from teachers of MAN in Tanah Datar while for the qualitative data was gotten from the school principals, vice school principals as well as teachers. Based on the research finding, it was found that in the madrasah activities planning was 82.11%; activities organizing was 79.50%; activities leading was 79.92%; activities actuating was 78.53%; and activities controlling was 81 %. In general, the competence of the madrasah principals of MAN in Tanah Datar was good in all aspect.